Essays in the economics of care - Altringer, Levi A., author; Braunstein, Elissa, advisor; Zahran, Sammy, advisor; Mushinski, David, committee member; Hempel, Lynn, committee member (Colorado State University. Libraries, 2022)
The Build Back Better legislation (H.R. 5376) currently being debated in Congress represents the first major attempt to build a care infrastructure that heavily invests in children and families, recognizing the value of care and care workers. The legislation (1) promotes recruitment, education, training, retention, and career advancements of direct care workers by providing competitive wages, benefits, and other support services to the direct care workforce; (2) establishes an entitlement program to provide qualifying families the opportunity to obtain high-quality child care; (3) allows states, almost entirely federally funded for the first three years, to provide universal preschool to 3- and 4-year-olds; (4) establishes universal paid family leave; (5) provides infrastructure grants to improve child care safety; (6) supplies child care wage grants for small businesses; (7) provides child care allowances as part of trade adjustment programs for workers; (8) makes permanent the expansion of the Child and Dependent Care Tax Credit provided by the American Rescue Plan Act of 2021; and (9) establishes payroll tax credit for child care workers and tax credits for caregiver expenses. In their own way, each chapter of this dissertation speaks to policies outlined in this legislation. In Chapter 1, titled The Role of Care Policy in Procyclical Child Mortality, I investigate the impact of the business cycle on child mortality. I conceptualize care as being supplied by three sectors---household, private, and public---and argue that public investment and provision insulates children from cyclical fluctuations in the quantity and quality of care provided. I then hypothesize that, in so far as the care mechanism mediates procyclical child mortality, children who are most likely to be the beneficiaries of generous care policy will be less exposed to the mortality risks of economic boom. Employing a sample of 21 OECD countries over the period 1960-2015, I show that procyclical mortality is null for children 5 to 9 years of age. This is the age group for which all OECD countries in my sample have universal, publicly provided care---i.e., primary education. Among children 0 to 4 years old, however, economic expansions are associated with increased risk of mortality. I then show that procyclical mortality among the 0- to 4-year-old age group is attenuated, and even disappears, in increasingly generous care policy environments. In Chapter 2, titled The Contemporaneous Mortality Benefits of the Head Start Program, I investigate the impact of Head Start on population-level child mortality. Though widely perceived as a schooling program focused on cognitive development, I argue that the "whole child" services provided by Head Start act as a de facto investment into the health and safety of poor children. The Head Start Expansion and Quality Improvement Act of 1990 led to considerable variation in program funding across localities. Further, program age requirements meant that increases in funding were largely directed toward the enrollment of 3- and 4-year-old children. Employing a sample of 50 large labor market areas over the period 1983 to 2007, I estimate log-log and log-linear fixed-effect mortality regressions and find that, relative to 1- to 2-year-olds, increases in Head Start funding are associated with reductions in 3- and 4-year-old mortality, all else equal. Then, utilizing that fact that children must also be poverty-eligible for Head Start, I show that the potential mortality benefits of Head Start are pronounced in relatively poor and disproportionately Black communities, as expected. In Chapter 3, titled Revisiting the Wages of Virtue and the Relative Pay of Care Work, I extend and update previous research by investigating the relative pay of care work in the National Longitudinal Survey of Youth 1997. Research in feminist and labor economics provide several theoretical rationale as to why workers in care occupations might receive lower wages. I employ three separate measures of care work and show the continued existence of wage penalties among nurturant care occupations, while there appears to be no wage penalty for workers in reproductive care occupations, all else equal. Testing for heterogeneous care penalties across the occupational skill distribution, I find that the wage penalty for nurturant care work increases in relatively high-skill occupations among men. Alternatively, the wage penalty for nurturant care work is null, if not a slight wage premium, in relatively high-skill occupations among women. I explore potential explanations for the inconsistent behavior of these estimated care penalties across gender, such as occupational crowding and selection via occupational segregation, or sorting. The findings of this chapter have important implications for care penalty literature and motivate potential avenues of future research.
Keywords: health; public; labor; care